Impact of cutting types and commercial plant growth regulators on the propagation of red star begonia (Begonia rex-cultorum) - Latifah, Zahrotul; Wurjani, Widi; Sutini, Sutini (Universitas Lancang Kuning, 2024)
Begonia is an ornamental plant known for its beautiful, variegated leaves. Propagation of this plant via vegetative means, particularly using leaves, often encounters challenges such as drying, rotting, and mortality of cuttings, necessitating the use of plant growth regulators (PGRs) to support their development. This study aims to determine the optimal combination of cutting type and commercial PGR concentration for the growth of red star begonia leaf cuttings. A factorial completely randomized design (CRD) was employed with two factors: cutting type (whole leaves and leaf slices) and PGR concentration (250 ppm, 300 ppm, 350 ppm, and 400 ppm), each replicated three times. The results indicated that the best combination for leaf number, root length, primary root number, and survival rate was whole leaves with a PGR concentration of 400 ppm. For the earliest sprout emergence, the best treatment was a PGR concentration of 350 ppm. These findings can enhance the efficiency of vegetative propagation of red star begonia, reduce propagation failure rates, and provide practical guidance for growers and ornamental plant enthusiasts in selecting optimal methods and PGR concentrations.